2012
DOI: 10.1128/jvi.00408-12
|View full text |Cite
|
Sign up to set email alerts
|

The Fanconi Anemia Pathway Limits Human Papillomavirus Replication

Abstract: k High-risk human papillomaviruses (HPVs) deregulate epidermal differentiation and cause anogenital and head and neck squamous cell carcinomas (SCCs). The E7 gene is considered the predominant viral oncogene and drives proliferation and genome instability. While the implementation of routine screens has greatly reduced the incidence of cervical cancers which are almost exclusively HPV positive, the proportion of HPV-positive head and neck SCCs is on the rise. High levels of HPV oncogene expression and genome l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 35 publications
2
57
1
1
Order By: Relevance
“…There is also considerable evidence that HPV oncogenes collaborate with FA deficiency to drive even greater cell proliferation. We have previously reported that HPV-immortalized FA keratinocytes form hyperplastic epithelium in an organotypic raft culture system compared to complemented cells (36,53). Furthermore, several studies have implicated FA in the increased incidence and aggressiveness of HPV-induced mouse models of cancer (54)(55)(56), and there is controversial evidence that HPV plays a role in the increased incidence of head, neck, and anogenital tumors in FA patients (57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…There is also considerable evidence that HPV oncogenes collaborate with FA deficiency to drive even greater cell proliferation. We have previously reported that HPV-immortalized FA keratinocytes form hyperplastic epithelium in an organotypic raft culture system compared to complemented cells (36,53). Furthermore, several studies have implicated FA in the increased incidence and aggressiveness of HPV-induced mouse models of cancer (54)(55)(56), and there is controversial evidence that HPV plays a role in the increased incidence of head, neck, and anogenital tumors in FA patients (57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, genetic variations in the repair proteins XRCC4 and Mre11A considerably increase the risk of HPV18 genome integration and possible tumorigenesis (Amirian et al 2012, Anacker et al 2014, Moody and Laimins 2009. Similarly, loss of the FANCD2 component of the FA pathway also facilitates viral replication (Hoskins et al 2012). Deficiencies in this pathway predispose to HPV-related head and neck cancer (Park et al 2010).…”
Section: Ddr Homologous Recombination and Pv Replicationmentioning
confidence: 96%
“…There is hence selection pressure against APOBEC3A expression during the malignant progression of HPV-negative tu- mors. This selective pressure is relieved in high-risk HPVpositive penile SCCs, in which the degradation of pRB and p53 [28], possibly in concert with other targets associated with DNA damage checkpoint signaling and repair [29,30], overrides negative growth-regulatory signals.…”
Section: Discussionmentioning
confidence: 99%